Distinct Clinicopathological Features and Prognosis of Helicobacter pylori Negative Gastric Cancer. - Kun-Feng Tsai; Jyh-Ming Liou; Mei-Jyh Chen; Chien-Chuan Chen; Sung-Hsin Kuo; I-Rue Lai; Kun-Huei Yeh; Ming-Tsan Lin; Hsiu-Po Wang; Ann-Lii Cheng; Jaw-Town Lin; Chia-Tung Shun; et al. (PLoS ONE)
Background Whether the characteristics and prognosis of gastric cancer (GC) are different in patients with and without Helicobacter pylori (HP) remains controversial. The definitions of HP status in patients with atrophic gastritis but negative tests for HP are heterogeneous. We aimed to assess the impact of HP on the prognosis of GC using different definitions. Methods From 1998 Nov to 2011 Jul, five hundred and sixty-seven consecutive patients with GC were included. HP status was determined by serology and histology. Patients with any positive test were defined as HP infection. Patients without HP infection whose serum pepsinogen (PG) I <70 ng/dl and PG I/II ratio < 3.0 were defined as atrophic gastritis and they were categorized into model 1: HP positive; model 2: HP negative; and model 3: exclusion of these patients. Results We found four characteristics of HP negative GC in comparison to HP positive GC: (1) higher proportion of the proximal tumor location (24.0%, P = 0.004), (2) more diffuse histologic type (56.1%, p = 0.008), (3) younger disease onset (58.02 years, p = 0.008) and (4) more stage IV disease (40.6%, p = 0.03). Patients with negative HP had worse overall survival (24.0% vs. 35.8%, p = 0.035). In Cox regression models, the negative HP status is an independent poor prognostic factor (HR: 1.34, CI:1.04-1.71, p = 0.019) in model 1, especially in stage I, II and III patients (HR: 1.62; CI:1.05-2.51,p = 0.026). Conclusion We found the distinct characteristics of HP negative GC. The prognosis of HP negative GC was poor.